Islamic Fintech Adoption and MSME Financial Inclusion in Indonesia - Noor Shodiq Askandar; Harun Alrasyid; Nafadzila Wahyuniar Asri (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2026)
Despite the rapid growth of Islamic financial technology (Islamic fintech), the access of micro, small and medium enterprises (MSMEs) to formal financial services continues to remain restrictive. This issue is important in Indonesia, where Islamic fintech offers Shariah-compliant digital access, yet MSMEs still face barriers of literacy, trust, and usability. This research examines how perceived usefulness and perceived ease of use influence MSMEs’ adoption of Shariah-compliant fintech and whether such adoption improves the financial inclusion of Indonesian MSMEs. Through a quantitative design, data were collected from 203 MSME owners and managers who had previous experience of Islamic fintech. The study tested both direct effects and the mediating role among constructs through Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that perceived usefulness and perceived ease of use can significantly encourage Islamic fintech adoption, with perceived ease of use being the strongest factor. Adoption, in turn, improves financial inclusion and partially mediates the relationship between technology-related perceptions and inclusive outcomes. The findings of this study enhance the Technology Acceptance Model in the Islamic fintech context and highlight that adoption serves as an important behavioural pathway for digital innovation to be used and participate financially. The key novelty of this study lies in positioning Islamic fintech adoption as a mediating mechanism between TAM-based perceptions and MSME financial inclusion. This study contributes to Islamic fintech literature by highlighting adoption as a novel mediating pathway through which technology-related perceptions enhance MSME financial inclusion.